Nano-co-delivery of lipophosphoglycan with soluble and autoclaved leishmania antigens into PLGA nanoparticles: Evaluation of in vitro and in vivo immunostimulatory effects against visceral leishmaniasis - Tosyali, Ozlem Ayse; Allahverdiyev, Adil; Bagirova, Melahat; Abamor, Emrah Sefik; Aydogdu, Mehmet; Dinparvar, Sahar; Acar, Tayfun; Mustafaeva, Zeynep; Derman, Serap (ELSEVIER, 2021)
The aim of the present study was to encapsulate lipophosphoglycan molecule (LPG) which is one of the most immunogenic antigens of Leishmania parasites into PLGA nanoparticles with autoclaved or soluble leishmanial antigens, characterize synthetized nanoparticles with different methods and evaluate their in vitro/in vivo immunostimulatory activities to develop new vaccine candidates. PLGA nanoparticles including LPG and autoclaved leishmania antigen (ALA) or soluble leishmania antigen (ALA) were synthetized by double emulsion solvent evaporation method. The synthetized nanoparticles were characterized by SEM and Zeta-sizer instruments for determination of size, zeta potentials and polydispersity index (PDI) values. The antigen release profiles and encapsulation efficiencies were determined by UV-Vis spectroscopy. Griess reaction and ELISA tests were used for measurements of produced nitric oxide (NO) and cytokine levels of macrophages and splenocytes treated with nanoparticles. For determination of protective effects of nanoparticles, parasite reduction in livers and spleens of immunized mice were calculated by LDU values post-infection. According to results, (SLA-LPG) PLGA NPs and (ALA-LPG) PLGA NPs possessed the sizes of 253 and 307 nm respectively. Antigen-loaded nanoparticles elevated the released NO amounts from macrophages for 14 and 18-folds in contrast to control. Furthermore, synthetized nanoparticles significantly triggered macrophages to produce excessive levels of IFN-gamma and IL-12 cytokines. Besides it was detected that vaccination of mice with (SLA-LPG) PLGA NPs and (ALA-LPG) PLGA NPs elicited approximately 80% protection from Visceral Leishmaniasis. Furthermore, (SLA-LPG) PLGA NPs and (ALA-LPG) PLGA NPs lead to 10 to 14-folds increase in secreted Th1 cytokine levels from splenocytes than control demonstrating abundantly stimulation of T cell response following to vaccination with nano-vaccine formulations. These results reveal that both (SLA-LPG) PLGA NPs and (ALA-LPG) PLGA NPs have excellent immunostimulatory activities and they are promising nanovaccine formulations for the prevention of leishmaniasis in near future.
Keywords: Leishmania; Antigen; PLGA; Nanoparticles; Vaccine; Delivery; CUTANEOUS LEISHMANIASIS; IMMUNE-RESPONSE; TYROSINE-PHOSPHATASE; MACROPHAGES; PROTECTION; IMMUNIZATION; MECHANISMS; ACTIVATION; INDUCTION; Materials Science